Anatomical Variations of the Gallbladder and Bile Ducts: An MRI Study - Kigundu Yason; Kirum Gonzaga Gonza; Okello Michael; Buwembo William; Ian Munabi; Kawooya Michael (International Journal of Hepatology)
Conclusion: The findings showed various anatomical variations that were slightly higher in the study population than those reported in the literature. This study emphasizes the critical need for comprehensive knowledge to enhance surgical safety, minimize iatrogenic trauma, and improve the accuracy of diagnostic imaging and hepatobiliary procedures.